The quintessence of lives intellectual biographies in the Low Countries presented to Jan Roegiers. - Delsaerdt, Pierre; Delville, Jean-Pierre, 1951-; Roegiers, Jan.; Schwall, Hedwig; Vanysacker, Dries (Turnhout Brepols, 2010)
"More than twenty-five historians have written intellectual biographies of figures who created a 'second life' for themselves on paper. All persons discussed are firmly rooted in the intellectual life of the Low Countries and were active there between the sixteenth and the twentieth century. The volume is offered on the occasion of the retirement of Prof. Dr. Jan Roegiers as full professor at the K.U. Leuven. . . .The contributions, mainly in English and French, but also in German and Dutch are written by Erik Aerts, Bruno Boute, Rob Brusten and friends, Luc Courtois, Pierre Delsaerdt, Jean-Pierre Delville, Wim Francois, Willem Frijhoff, Lieve Gevers, Craig Harline, Guido Hendrix, Marion Huibrechts, Staf Janssens, Eddy Louchez, Jeroen Nilis, Ernest Persoons, Eddy Put, Toon Quaghebeur, Ludo Simons, Violet Soen, Gilbert Tournoy, Michel van Meerbeeck, Dries Vanysacker, Johan Verberckmoes, Tom Verschaffel, Dries Welkenhuyzen, and Kaat Wils." p. 4 of cover.
Keywords: 920.0492 -- History Biographies Netherlands; 378.4 <493 KUL> <082> -- Universiteiten--België--Feestbundels. Festschriften--KUL; 929 <491.9> -- Biografie. Genealogie. Heraldiek--De Nederlanden. Benelux; 929 <493> -- Biografie. Genealogie. Heraldiek--België; 949.19 <082> -- Geschiedenis van de Nederlanden, van de Benelux--Feestbundels. Festschriften; Belgium -- Biography; Belgium -- Intellectual life; Netherlands -- Biography; Netherlands -- Intellectual life; Festschrift - Libri Amicorum